PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SD NEGERI 066050 TEGAL SARI MANDALA KECAMATAN MEDAN DENAI - Pelita Angel Manalu; Dyan Wulan Sari HS; Patri Janson Silaban; Bogor Lumbanraja; Anton Sitepu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the influence of the Problem Based Learning learning model on the learning outcomes of science science students in grade IV of SD Negeri 066050 Tegal Sari Mandala, Medan Denai District, Academic Year 2024/2025. This study uses a quantitative research method. The population of this study is all grade IV students of SD Negeri 066050 Tegal Sari Mandala which consists of 1 class with a total of 30 students. Sampling using non-probability sampling, namely saturated sampling and a sample of 30 students. To find out the learning outcomes of students, the researcher conducted a pretest with an average score of 53,467, which is included in the poor category. After the research using the Problem Based Learning learning model, the results increased with an average score of 84,4 which was included in the very good category. It is said to have increased, as evidenced by the results of the calculation of the correlation coefficient test of 0.918, meaning rcal (0.918) ≥ rtable (0.361). Therefore, there is a strong influence between the Problem Based Learning learning model on student learning outcomes in grade IV of SD Negeri 066050 Tegal Sari Mandala. Judging from the results of the t-test test, which is 12,291 ≥ 1,697, it is declared that Ha is accepted. This shows that there is a significant positive influence of the use of the Problem Based Learning learning model on the learning outcomes of science and science students in grade IV of SD Negeri 066050 Tegal Sari Mandala, Medan Denai District, Academic Year 2023/2024.